De novo erectile dysfunction after anterior urethroplasty: a systematic review and meta-analysis - Blaschko, Sarah D. (2013)
OBJECTIVE: To evaluate the likelihood of developing de novo erectile dysfunction (ED) after anterior urethroplasty and to determine if this likelihood is influenced by age, stricture length, number of previous procedures or timing of evaluation. MATERIALS AND METHODS: PubMed, Embase, Cochrane, and Google Scholar databases were searched for the terms `urethroplasty', `urethral obstruction', `urethral stricture', `sexual function', `erection', `erectile function', `erectile dysfunction', `impotence' and `sexual dysfunction'. Two reviewers evaluated articles for inclusion based on predetermined criteria. RESULTS: In a meta-analysis of 36 studies with a total of 2323 patients, de novo ED was rare, with an incidence of 1%. In studies that assessed postoperative erectile function at more than one time point, ED was transient and resolved at between 6 and 12 months in 86% of cases. CONCLUSIONS: Men should be counselled regarding the possibility of transient or permanent de novo ED after anterior urethroplasty procedures. Increasing mean age was associated with an increased likelihood of de novo ED, but this was not statistically significant.